A flow cytometry-based screen for synthetic riboswitches - Lynch, Sean A. (Oxford University Press, 2009)
Riboswitches regulate gene expression through direct, small molecule–mRNA interactions. The creation of new synthetic riboswitches from in vitro selected aptamers benefits from rapid, high-throughput methods for identifying switches capable of triggering dramatic changes in gene expression in the presence of a desired ligand. Here we present a flow cytometry-based screen for identifying synthetic riboswitches that induce robust increases in gene expression in the presence of theophylline. The performance characteristics of our newly identified riboswitches exceed those of previously described natural and synthetic riboswitches. Sequencing data and structure probing experiments reveal the ribosome binding site to be an important determinant of how well a switch performs and may provide insights into the design of new synthetic riboswitches.